2012
DOI: 10.1007/s00431-012-1884-4
|View full text |Cite
|
Sign up to set email alerts
|

Change in flatfoot of preschool-aged children: a 1-year follow-up study

Abstract: The 1-year follow-up found that some preschool-aged children with flatfoot may develop normal feet, while children with normal feet may begin to experience the signs. Relevant factors affecting flatfoot in preschool-aged children continue to require further clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…A flatfoot appearance is normal in the first decade of life, reducing by age 10. Flatfoot is more common in boys, overweight/obesity and younger children, and it varies with ethnicity …”
Section: Children's Foot and Leg Concernsmentioning
confidence: 99%
“…A flatfoot appearance is normal in the first decade of life, reducing by age 10. Flatfoot is more common in boys, overweight/obesity and younger children, and it varies with ethnicity …”
Section: Children's Foot and Leg Concernsmentioning
confidence: 99%
“…Despite the importance of the developing foot, there is limited research examining the effects of obesity on foot structure and function in preschool aged children [49][50][51][52][53]. In our research we found that relative to their non-overweight counterparts, overweight/obese preschool children (4.3 ± 0.6 years of age) have significantly larger dimensions for foot length, ball of foot length, instep length, ball of foot breadth, heel breadth, and instep and ball of foot circumferences [52] (Fig.…”
Section: Effects Of Obesity In Young Children On Foot Structurementioning
confidence: 98%
“…The study of the footprint was obtained by a pedograph. Three measurements were used: Clarke's angle, the Chippaux-Smirak index, and the Staheli arch index [6][7][8].…”
Section: Flat Foot Diagnosticmentioning
confidence: 99%
“…Footprint analysis using a pedograph is a simple, swift, and cost-effective method. The three measurements habitually used in the diagnosis of flat foot using a pedograph are: Clarke's angle [6] the Chippaux-Smirak index [7] and the Staheli index [8].…”
Section: Introductionmentioning
confidence: 99%